Automobiles: a static technology, a "wait-and-see" industry?. (1st January 1998) - Chanaron, Jean-Jacques
This paper presents a global analysis of the key factors that could determine the scope of technological innovation in the automotive industry. It argues that most social, economic, industrial and technical features of this industry play against any radical innovation such as, for example, the electric vehicle. It emphasises the "blocking" role of heavy capital investment, massive employment, infrastructure, consumers' constraints, etc. It contributes to the theoretical debate on technological inertia.